Achievable Information Rate in Nonlinear WDM Fiber-Optic Systems With Arbitrary Modulation Formats and Dispersion Maps - Secondini, Marco; Forestieri, Enrico; Prati, Giancarlo (Journal of lightwave technology, 2013)
The problem of analytical evaluation of the maximum rate at which information can be reliably transmitted on a nonlinear wavelength division multiplexing fiber-optic channel with a given modulation format and detection strategy is addressed. An approximate solution of the nonlinear Schrödinger equation is adopted to obtain an accurate analytical discrete-time channel model, valid for arbitrary link configurations and modulation formats. By exploiting the concept of mismatched decoding, considering a sub-optimum detection strategy that accounts for intra-channel nonlinearities, the proposed model is employed to derive closed-form expressions of the achievable information rate with various modulation formats. All the analytical results are verified through comparison with numerical simulations in different scenarios.